Perbedaan efektifitas senam ergonomik dan senam aerobik terhadap ansietas penderita diabetes melitus tipe 2 pada masa pandemi Covid-19 di kota Bukittinggi - Dian Anggraini; Suri Silvia Intan (Institut Kesehatan dan Teknologi Al Insyirah, 2022)
Currently, the Covid-19 outbreak continues to increase in Indonesia, especially in West Sumatra. The level of morbidity and mortality is dominated by patients who have comorbidities, one of which is diabetes mellitus. This condition causes people with diabetes mellitus to experience anxiety. So the need for an intervention to overcome anxiety in diabetics. One of the nursing interventions that nurses can do is physical exercise such as ergonomic exercise and aerobic exercise. The purpose of this study was to determine the difference in the effectiveness of ergonomic exercise and aerobic exercise on anxiety in patients with type 2 diabetes mellitus during the Covid-19 pandemic. The research method used is a quasi-experimental method consisting of two treatment groups. Where the first group was treated with aerobic exercise while the second group was given treatment in the form of ergonomic exercise. The population in this study were people with type 2 diabetes mellitus with a sample of 18 people for each group. The instrument used is a quesionnaire and standard operating procedures. The results showed that skoring of anxiety was 16,83 in the aerobic exercise group and 16,22 in the ergonomic exercise group. Based on the results of the T-Independent test, aobtained p value of 0.940 was, which means that there is no difference in the effect of aerobic exercise and ergonomic exercise on anxiety in DM patients. It is expected that health workers can provide nursing implementation in the form of physical activity to lower anxiety of DM patients